Iatrogenic ventricular septal defects following transcatheter aortic valve implantation. Issue 1 (2nd January 2023) - Urbanczyk, Jonathan P.; Mixon, Timothy A.; Konda, Subbareddy; Caldera, Angel E.
Abstract: Ventricular septal defect (VSD) rarely occurs following transcatheter aortic valve implantation (TAVI). We report two patients who developed VSD following TAVI. One case was a Gerbode defect treated by percutaneous closure, and the second was a restrictive perimembranous VSD managed conservatively.